1986
DOI: 10.1136/pgmj.62.729.621
|View full text |Cite
|
Sign up to set email alerts
|

Meningism following Salmonella virchow food poisoning

Abstract: Summary:Thirty six patients were admitted to hospital as a result of Salmonella virchow infection during an outbreak of food poisoning in Essex in 1984. Out of 12 patients with evidence of bloodstream invasion, one third presented primarily with meningism and attention is drawn to this unusual clinical picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A previous study in the United Kingdom reported that S. Virchow caused eight cases of bacteremia in adults; although none of the patients developed meningitis, all were secondary to gastroenteritis and two had a travel history in Spain [ 12 ]. In addition, three cases of meningitis following S. Virchow food poisoning in adults were reported in the United Kingdom [ 13 ] and one case was documented in Scotland in an 18-year-old patient [ 14 ]. Furthermore, two cases of meningitis caused by S. Virchow have been described in Sweden and in Germany [ 4 , 15 ] which shared some features with the case in Italy in that both the patients travelled abroad (Thailand and Denmark, respectively), were not part of an outbreak and the source of infection remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in the United Kingdom reported that S. Virchow caused eight cases of bacteremia in adults; although none of the patients developed meningitis, all were secondary to gastroenteritis and two had a travel history in Spain [ 12 ]. In addition, three cases of meningitis following S. Virchow food poisoning in adults were reported in the United Kingdom [ 13 ] and one case was documented in Scotland in an 18-year-old patient [ 14 ]. Furthermore, two cases of meningitis caused by S. Virchow have been described in Sweden and in Germany [ 4 , 15 ] which shared some features with the case in Italy in that both the patients travelled abroad (Thailand and Denmark, respectively), were not part of an outbreak and the source of infection remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…During the Edinburgh outbreak of 1983, 8 nine of the 15 patients with clinical septicaemia were found to have positive blood cultures, while in a large outbreak of 297 cases in mid‐Essex in 1984, 9 11 of 14 patients with clinical septicaemia likewise had 5 virchow blood cultures. However, in none of these well‐documented occurrences of S virchow was cholecystitis a reported feature.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal examination and sigmoidoscopy were normal. Investigations revealed a haemoglobin concentration of 14.7 g/dl, and a leucocyte count of 9.4 × 10 9 . A blood film showed toxic granulation of neutrophils.…”
Section: Case Reportmentioning
confidence: 97%